높은 신체활동 강도를 요구하는 젊은 환자에서 발생한 족관절의 내, 외측 동시 불안정증에 대한 수술적 치료: 증례 보고 - 최준영; 서진수; Jun Young Choi; Jin Soo Suh (대한족부족관절학회지, 2025)
Multidirectional joint instability is a condition where laxity occurs in two or more directions. This condition typically arises congenitally or because of hypermobility or repetitive, excessive physical activity. It can also occur from chronic damage to the joint capsule and multiple ligaments, causing a breakdown in stability. Despite the numerous studies conducted on multidirectional instability of the shoulder, there is a lack of published research on multidirectional instability of the ankle. This paper reports the case of a male patient in his early 30s, engaged in high-demand physical activity, who presented with simultaneous medial and lateral ankle instability. The patient underwent a combination of procedures, including an anterior talofibular ligament reconstruction with suture tape, deltoid ligament reattachment with suture anchors, anteroinferior tibiofibular ligament reconstruction with suture tape, and syndesmotic screw fixation with Tightrope insertion. The patient was followed up for one year postoperatively. This paper reports the clinical outcomes with a review of the relevant literature.